Morphometric Analysis of Sumatran, Kalimantan, and Javan Cyrtodactylus, which were Labelled as Cyrtodactylus marmoratus, Revealed Undescribed Species - Muhammad Alif Fauzi; Awal Riyanto; Nia Kurniawan (Journal of Tropical Biodiversity and Biotechnology, 2022)
Cyrtodactylus marmoratus is originally described based on the specimen from Java. Due to the marbled body colour pattern and the similarity in morphology, many specimens from outside of Java have been identified as C. marmoratus. The ongoing research, both molecular and morphological studies, showed that C. marmoratus is restricted to Java. The taxonomic status of specimens labelled as C. marmoratus from outside Java remains unresolved. Here, we study the morphometric and meristic of Javan, Sumatran, and Kalimantan Cyrtodactylus which were labelled as C. marmoratus to reveal their taxonomic status. We examined 11 morphometric and 19 meristic characters in 51 specimens at Museum Zoologicum Bogoriense (MZB) originally from, Java, Sumatra, and Kalimantan labelled as C. marmoratus as well as other recognized species. Principal Component Analysis (PCA) results show that C. marmoratus from Java differs from previous specimens which labelled as C. marmoratus from Sumatra and Kalimantan. The PCA results also show that C. marmoratus from Martabe differs from C. marmoratus Java which is supported by statistical analysis on interorbital, HeadW, HeadD, tubercle on the ventrolateral fold, dorsal tubercle and ventral scales. We hypothesized that Cyrtodactylus from Martabe is a suspected undescribed species-await formal description, and overall molecular analyses are needed for future study.